2022
DOI: 10.1007/s12519-022-00574-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between hospital- and community-acquired septic shock in children: a single-center retrospective cohort study

Abstract: Background We explored the differences in baseline characteristics, pathogens, complications, outcomes, and risk factors between children with hospital-acquired septic shock (HASS) and community-acquired septic shock (CASS) in the pediatric intensive care unit (PICU). Methods This retrospective study enrolled children with septic shock at the PICU of Beijing Children’s Hospital from January 1, 2016, to December 31, 2019. The patients were followed up until… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
1
1
0
Order By: Relevance
“…In our results, the proportion of boys with sepsis was higher than that of girls, which was consistent with the results of a single-center retrospective study in China (15). However, the results of our univariate logistic regression analysis suggested that there was no significant correlation between sex and sepsis mortality, similar to the findings of de Souza et al ( 16) and Boeddha et al (17).…”
Section: Discussionsupporting
confidence: 92%
“…In our results, the proportion of boys with sepsis was higher than that of girls, which was consistent with the results of a single-center retrospective study in China (15). However, the results of our univariate logistic regression analysis suggested that there was no significant correlation between sex and sepsis mortality, similar to the findings of de Souza et al ( 16) and Boeddha et al (17).…”
Section: Discussionsupporting
confidence: 92%
“…Study quality was de ned as poor (0-3), fair (4-6) or good (7)(8)(9). The quality of the included cohort studies is presented in Table 1 [11][12][13][16][17][18][19][20][21][22][23][24][25]. Westphal 2019 [20] Padro 2019 [13] Rhee 2019 [21] Baghdadi 2020 [22] Baghdadi 2020 [23] Di Giuseppe 2020 [24] and standard deviation with an calculator according to the sample size [27], and then performed meta-analysis.…”
Section: Quality Assessmentmentioning
confidence: 99%